2005
DOI: 10.1159/000086368
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Mini-Nutritional Assessment Scores with Age and Some Hematological Variables in Elderly Institutionalized Patients

Abstract: Background: Nutritional imbalance is a serious problem in developing countries, especially for the older population, which makes simple and rapid instruments for nutritional evaluation very necessary in order to have a detailed picture of the undernutrition epidemiology in those places. Objective: This work aimed to evaluate the nutritional status of elderly institutionalized patients by use of the Mini-Nutritional Assessment (MNA) test and compare the MNA scores with some hematological variables. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
4
5
2
1
Order By: Relevance
“…Malnutrition was proportional to older age when compared with younger groups. This affirmation concurs with that reported by Alves de Rezende et al and Cuervo et al [26,28], who also observed that older adult nutritional status was affected in relation to increased age. This is consistent with the observed age-dependent decrease of certain serum variables.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Malnutrition was proportional to older age when compared with younger groups. This affirmation concurs with that reported by Alves de Rezende et al and Cuervo et al [26,28], who also observed that older adult nutritional status was affected in relation to increased age. This is consistent with the observed age-dependent decrease of certain serum variables.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study are similar to those reported by Alves de Rezende et al and PereidaMachado and Santa Cruz-Coelho [26,27]. Using the same MNA instrument, they classified nutritional status in OAEF in their respective studies as follows: malnourished 8.3% and 15.3%, at risk of malnutrition 45.7% and 55.6%, and normal nutritional status 36% and 29.1%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3,29 Another study clearly demonstrated a significant correlation between the MNA test and laboratory parameters indicating hematological disorders. 30 However, this research concerned elderly people living in nursing homes, not cancer patients. In our study, we found that the MNA test was correlated with Hb and Htc.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Bak›mevinde kalanlarda ve hastanede yatan yafll›larda malnütrisyon riski ve malnütrisyon daha s›kl›kla gözlen-mektedir. [13][14][15] Epidemiyolojik çal›flmalara bak›ld›¤›nda toplum içinde yaflayan yafll›lar›n %5-10'unda malnütris-yon mevcuttur. Akut hastal›k için hastaneye yat›r›lanlar-da bu oran %26'ya ve bak›m evinde kalan ve uzun süreli bak›m alanlarda %30-60'lara ç›kar.…”
unclassified